Latvian Semigallia: what the Place Names Testify - Balode, Laimute (Acta humanitarica academiae Saulensis, 2025)
The article summarizes hypotheses of the origin of place names and the primary semantics of toponyms of the current Semigallia (Lat. Zemgale) – one of the historical ethnographic regions of Latvia. The short history of Semigallian cities and the possible etymology of names are introduced: city names such as Auce are discussed (mentioned in historical documents in 1426, place name of Baltic/Lithuanian origin), Bauska (mentioned in 1443, a city name possibly of Baltic/Latvian origin), Dobele (mentioned in 1254, toponym of Baltic/Latvian origin), Jelgava//Mītava (mentioned in 1265, place name of hypothetical – Livonian? Latvian? origin), Kalnciems (mentioned in 16th c., a place name of clear Latvian origin), Tukums (mentioned in 1253, a place name of very obscure – possibly Livonian, or Latvian – origin). Names of the largest rivers in Latvian Semigallia are also analyzed – Lielupe, Mūsa, Mēmele, as well as the names of some tributaries (Kaucīte, Īslīce, Svitene, Sesava, Platone, Svēte, etc.). Particularly distinctive is the derivative suffix -aine: Cērpaine, Svēpaine, Skujaine, Svētaine, Krievaine, Govaine, etc. The article also briefly discusses the oikonyms and microtoponyms of Semigallia, among which there are a number of borrowings. The main attention is paid to Lithuanianisms, which are most abundant on the Lithuanian-Latvian border: river names Ģirupe, Žare, Žurele, meadow name Ežerelis, home-stead names Karvišķe, Veršūns. Possible Lithuanianisms are evidenced by both the phonetics of names (homestead names Ķišķi, Žinduls) and morphology (Adžūni, Gaidžūni, Juknišķi). The phonetic feature of the Semigallian dialect – anaptyxis (insertion of a short vocal sound after tautosyllabic r/l) – is recorded in the Semigallian placenames: Zirega dzelme, Stirenu pļavele, Karepu dīķis. Semigallian toponyms (especially microtoponyms) stand out with a characteristic suffix -ene: oikonyms Blīdene, Spārnene, Zebrene, Dobele < * Dobelene, Tērvete < *Tērvetene, meadow names Cepurene, Griķene, Puķene, Talcene, Līdzumene, Mazā dakterene and many others.